Business incubators as allied in reducing the transaction costs in Mexican entrepreneurs - Vargas-Hernández, José G; Garcia Magaña, Rosa del Sagrario (Journal of Entrepreneurship, Business and Economics; Vol 2 No 2 (2014), 2014)
Purpose- Strategic alliances are given by voluntary agreement between the parties, and have various forms, means and objectives which exist. In this text, the incubators as potential allies for entrepre-neurs in the creation process of the company and as a cause of reduction of transaction costs in the process, where the relationship between the two sides have discussed them generates benefits of vari-ous natures. While it is not set as the union of both, if it looks like the relationship and close contact, as a network, which allows the incubator to survive and achieve its objective and entrepreneurial reduce the risk of birth as a company, in addition to build networks with other companies, organiza-tions or institutions and ease of financing, and even the possibility of investors. Design/methodology/approach- The method used for this paper is based on the analyses of official documents of the institutions referred, some studies on entrepreneurship and startups, and finally available data on new firms and institutions as RedJal and INEGI. In addition, incubators and studies on such cases were also reviewed to learn about the experience, services and working methods of these. This focused on observing what happens in Mexico about. Findings- Business incubators in Mexico use to be strategic partners for entrepreneurs that enable the latter to reduce their transaction costs to startup a new company. Business incubators are also important to reduce the risk of death of the company and reduce uncertainty in the process. Also, the services provided, experience and expertise by incubators are important for a growing business arises with the required formality and according to the law, of course protecting its intellectual property and creating an image that pays to create its own reputation. Conceptual Paper Reference to this paper should be made as follows: Vargas-Hernández, J. G., and Garcia Magaña, R.S. (2014). “Business incubators as allied in reducing the transaction costs in Mexican entrepre-neurs”, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 2, pp. 1–9.